Work-Family Conflict and Innovative Teaching Among Indonesian Teachers: The Mediating Role of Organizational Commitment - M. Riadhos Solichin; Eka Hendi Andriansyah; Fibria Cahyani; Dudung Ma’ruf Nuris; Mohamad Arief Rafsanjani; Rina Rachmawati (International Journal of Emerging Research and Review, 2023)
This research sought to examine the relationship between work-family conflict, organizational commitment, and innovative teaching skills among Indonesian teachers. At the same time, few studies use job stressors such as work-family conflict as a predictor of innovative teaching skills. This study also presents an organizational commitment in getting a deeper understanding of the research model. Method: This research utilized PLS-SEM to examine the research model on 273 senior high school teachers as research participants. Result: The result shows that work-family conflict negatively affects innovative teaching and organizational commitment. Meanwhile, organizational commitment positively affects innovative teaching. Furthermore, organizational commitment plays a mediating variable in the link between work-family conflict and innovative teaching. Novelty: This study will enrich our understanding regarding the predictor of innovative teaching among Indonesian teachers through another standpoint, the job stressors in the form of work-family conflict. This study also presents an organizational commitment to give a deeper understanding on how the mechanism of work-family conflict affects the innovative teaching skills of the teacher.